The development of realistic mathematics education-based student worksheets to enhance higher-order thinking skills and mathematical ability - Sutarni, Sri; Sutama, Sutama; Prayitno, Harun Joko; Sutopo, Anam; Laksmiwati, Pasttita Ayu (IKIP Siliwangi and I-MES, 2024)
This study aims to provide educational resources in the form of worksheets based on Realistic Mathematics Education (RME) principles and focus on the topic of equal fractions. The main criteria for these resources are validity, feasibility, and effectiveness. The development methodology employed in this study is the ADDIE model, which encompasses the Analysis, Design, Development, Implementation, and Evaluation stages. The participants of this study consisted of 14 pupils enrolled in class IV at SDM Alam Surakarta. The assessment tools employed consisted of assessments on student learning outcomes about equivalent fractions and supplementary materials in the form of questionnaires, interview guides, and observation sheets. The examination of the data reveals that the learning tools have achieved a high level of validity, falling inside the extremely valid category, with an average score of 4.26. The feasibility test for the LKS, conducted by the assisting instructor, yielded an average score of 4.4. The pupils' performance on the LKS assessment yielded an average score of 4.89, placing them in the